Put focus on mental health issues to keep campus safe. Issue 12 (April 2017) - Hope, Joan
Abstract : Richard Beary, chief of police at the University of Central Florida, believes in keeping his campus safe by addressing the core problems that lead to crime and create safety challenges. And the biggest problem campus police units face is mental health issues. About 30 percent of people who are shot by law enforcement officers have mental health problems, Beary said. And on a large campus like UCF, many students struggle with mental health challenges. "The majority of our cases have young people who know they need help and are trying to get it, " Beary said. Campus officials can't just say, "See you in nine weeks [for a counseling appointment], " he added.